A new species of genus Tephritis Latreille and a new distribution record of genus Urophora Robineau-Desvoidy, from India - Singh, Maneesh Pal; Daroch, Rakesh; Korneyev, Severyn V.; Sharma, Isha (Zootaxa, 2023)
A new species of Tephritis Latreille, Tephritis himalayae Maneesh and Korneyev, sp. n. is described from the higher hills of Himachal Pradesh (India). The species was found breeding on the very common orchard weed Cirsium falconeri (Hook.f.). The new species belongs to the hyoscyami-conura group of species and is very closely related to T. cardualis Hardy. An identification key for the genus Tephritis known from the Indian subcontinent is given. In addition, Urophora terebrans (Loew), a Palearctic species, is recorded from the mid-hills of Himachal Pradesh, India. Illustrations for both species are given.